2020
DOI: 10.2147/ijwh.s220523
|View full text |Cite
|
Sign up to set email alerts
|

<p>Transcutaneous Electrical Nerve Stimulation (TENS) for Primary Dysmenorrhea: An Overview</p>

Abstract: Primary dysmenorrhea is a chronic health condition that affects primarily young women. Transcutaneous electrical nerve stimulation (TENS) has been suggested as an effective pain reduction modality in primary dysmenorrhea. TENS is a noninvasive, inexpensive, portable method with minimal risks and a few contraindications. When necessary, it can be self-administered on a daily basis during everyday activities. Several studies have investigated the effectiveness of TENS in reducing pain, decreasing the use of anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…An animal study had correspondingly focused on the effect of TENS on the process of wound healing from the perspective of proinflammatory cytokine expression and had found that TENS had significantly mitigated the immunoreaction of TNFα, IL-1β, and IL-6 in the dermis compared with other treatments, indicating that TENS had shortened the healing process by inhibiting the inflammatory responses [121]. Meanwhile, studies had verified the effectiveness of TENS in reducing menstrual pain and improving the quality of life in patients with dysmenorrhea [122][123][124]. Compared with treatment methods such as acupuncture, TEAS has also eased restrictions on in-hospital treatment.…”
Section: Recommendations For Future Researchesmentioning
confidence: 99%
“…An animal study had correspondingly focused on the effect of TENS on the process of wound healing from the perspective of proinflammatory cytokine expression and had found that TENS had significantly mitigated the immunoreaction of TNFα, IL-1β, and IL-6 in the dermis compared with other treatments, indicating that TENS had shortened the healing process by inhibiting the inflammatory responses [121]. Meanwhile, studies had verified the effectiveness of TENS in reducing menstrual pain and improving the quality of life in patients with dysmenorrhea [122][123][124]. Compared with treatment methods such as acupuncture, TEAS has also eased restrictions on in-hospital treatment.…”
Section: Recommendations For Future Researchesmentioning
confidence: 99%
“…As such, the results of the present study may contribute to the PD research agenda. Although TENS is used to treat PD symptoms [ 16 ] and has been shown to reduce pain with minimum adverse effects [ 15 ], the studies are considered of low to moderate quality [ 16 ] and lack information on parameters and clinical considerations [ 15 ], which makes it difficult to compare results and to establish the best parameters of electrical stimulation. Understanding whether TENS is really cost-effective for PD pain treatment opens possibilities to include this resource as a recommendation, and with that, call the attention of both professionals and women to the fact that PD can be treated.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, they may present a failure rate of 20-25% and adverse effects such as indigestion, headaches, and drowsiness [10]. Consequently, nonpharmacological alternatives may be used to obtain symptom relief; the most common are regular physical activity [11], topical heat [12], acupuncture [13], and transcutaneous electrical nerve stimulation (TENS) [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prostaglandins can cause severe uterine contractions, fatigue, dizziness, headache, nervous change and other related symptoms (5)(6)(7). There are several treatments for primary dysmenorrhea and associated symptoms, including contraceptive pills (8,9), vitamin E compounds (10), vitamin D (10)(11)(12), sh oil supplements (13), diet (14), exercise and physical activity (15), acupuncture (16), topical heat (17), psychotherapy (18) and Nonsteroidal anti-in ammatory drugs (NSAIDs).…”
Section: Introductionmentioning
confidence: 99%